A new species of the genus Stigmaeus (Acari: Trombidiformes: Stigmaeidae) from North of Iran - Mohammad Bagheri; Forough Ranjbar-Varandi; Mohsen Yazdanian; Shila Shirinbeik Mohajer (Persian Journal of Acarology)
A new species of the genus Stigmaeus, Stigmaeus sariensis Bagheri sp. nov., collected from soil under Oak trees (Quercus sp.) and on moss, is described and illustrated from Sari city, Mazandaran province, Iran